Academic Self-Efficacy and Its Relationship With Academic Performance in Nutrition Students - Rosales-Ronquillo, Cynthia Anahi; Hernández-Jácquez, Luis Fernando (Revista Electrónica Educare, 2020)
This paper shows the results of a research study whose main objectives were to determine the level of perceived academic self-efficacy and identify the relationship between self-efficacy and academic performance in all students (391) of the Nutrition Degree program of a faculty in the state of Durango, Mexico. Taking Albert Bandura’s theory of self-efficacy as a theoretical basis, a quantitative, non-experimental, and transversal research study. A survey was applied, and the results obtained showed that the students present a high level of academic self-efficacy and that there is a positive relationship between this self-efficacy and the students’ academic performance. It is recommended to intervene in aspects such as concentration, attention, and confidence to exchange points of view with the teacher; all these aspects showed low self-evaluations.